Chlorine in NiO promotes electroreduction of CO2 to formate. (August 2022) - Rodriguez-Olguin, M.A.; Flox, C.; Ponce-Pérez, R.; Lipin, R.; Ruiz-Zepeda, F.; Winczewski, J.P.; Kallio, T.; Vandichel, M.; Guerrero-Sánchez, J.; Gardeniers, J.G.E.; Takeuchi, N.; Susarrey-Arce, A.
Highlights: A solid-state synthesis approach for the production of a NiO electrocatalyst is introduced. The NiO functionality is demonstrated during the electrochemical reduction of CO2 . Advanced characterization and density-functional theory are combined to unveil the reaction mechanism of CO2 RR to formate. Cl plays a key role in introducing uncoordinated species in NiO, promoting the reduction of CO2 to formate. Abstract: We report the exceptional finding that NiO, a known electroactive catalyst for the reduction of CO2 to CO, can be tuned to become an active electrocatalyst for CO2 reduction to formate when chlorine is synthetically incorporated into NiO. The CO2 reduction reaction (CO2 RR) is carried out on chlorine-containing NiO octahedral particles made by a solid-state synthesis method yielding a Faradaic efficiency (FE) of 70 % for formate production at -0.8 V vs. RHE with a partial current density of 14.7 mA/cm 2 . XPS confirms the presence of Ni 3+ and Ni 2+ species, indicating the existence of uncoordinated Ni. The Ni 3+ /Ni 2+ ratio increases with the Cl concentrations on NiO. Cl concentrations are also confirmed with STEM-EDX. DFT modeling provides insights into the thermodynamic stability and CO2 RR mechanism over the Cl-containing NiO surface. It is suggested that Cl can occupy the defective sites created by oxygen vacancies on the NiO model with Cl (O-alpha+Cl). The surface Pourbaix diagrams constructed from DFT indicate the preferred surface terminations favorable at the operating conditions for the CO2 RR, which closely agrees with the experimental findings. The O-alpha+Cl has been found to promote CO2 RR to formate. Our results create new possibilities in the development of earth-abundant electrocatalysts for selective CO2 RR Graphical abstract: Image, graphical abstract .